Subchronic Toxicity Test of Indian Almond (Terminalia catappa) Leaves Water Extract on The Liver Histology of Mice (Mus musculus) - Nugroho Rudy; Ni Cening Sri Puspa; Retno Aryani; Widha Prahastika; Rudianto Rudianto; Hetty Manurung (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Indian almond (Terminalia catappa) is used as an alternative medicine by the community to treat various diseases. However, limited research has been conducted on the subchronic toxicity of Indian almond water extracts on the liver. Present study aimed to determine the subchronic toxic effects of Indian almond leaf water extract on the liver histology of mice and to evaluate the safe dose of Indian almond leaf water extract with various doses (125, 250, 500, 750 and 1000 mg/kg). Methods: In total of 33 male mice were randomly divided into 11 groups, each group consisting of three mice as replication. For 30 days, mice in five treatment groups were orally treated every day with water extracts of green Indian almond leaf while other five groups were given water extracts of brown Indian almond leaves and compare with control group. At the end of day 30, all mice were sacrificed, and hepar was taken out for histological preparations. The histopathological changes in the liver was observed and assessed based on histological damage in the term of degeneration and necrosis. Results: The administration of green and brown Indian almond water extract at doses of 125, 250, 500, 750 and 1000 mg / kg BB showed a toxic effect on the liver of mice. The toxic effect was due to the high doses, causing a cell swelling damage and increased liver necrosis. Conclusion: Indian almond leaf water extract can cause toxic effects on the liver of mice at the doses implemented.